Evaluasi Pengukuran Kekakuan Limpa dalam Memprediksi Perdarahan Varises Esofagus Berulang pada Pasien Sirosis Hati - Tahir, Andi Cahaya; Kurniawan, Juferdy; Simadibrata, Marcellus; Rizka, Aulia; Shatri, Hamzah; Lesmana, Cosmas Rinaldi A.; Mulansari, Nadia Ayu (UI Scholars Hub, 2024)
Introduction. Esophageal variceal bleeding is one of the complications caused by an increase in pressure within the portal vein blood vessels. The gold standard examination for portal pressure is the hepatic venous pressure gradient (HVPG), but HVPG examination is invasive, involving transjugular catheterization of the hepatic vein. Currently, non-invasive methods for measuring portal hypertension are being developed to predict esophageal varices and esophageal variceal bleeding using spleen stiffness measurements. This study aimed to evaluate the accuracy of spleen stiffness measurement in predicting recurrent esophageal variceal bleeding in patients with liver cirrhosis. Methods. This study used a retrospective cohort design with secondary data sourced from medical records at Cipto Mangunkusumo Hospital. Spleen stiffness assessment was conducted using the vibration controlled transient elastography (VCTE) spleen-dedicated stiffness measurement (FibroScan®, Echosens, France) with a frequency of 100Hz. After six weeks post-first esophageal variceal bleeding in liver cirrhosis patients, an evaluation of recurrent esophageal variceal bleeding was performed. The collected data were analyzed using SPSS 26. The ability of spleen stiffness measurement to predict recurrent esophageal variceal bleeding was assessed by evaluating the AUROC (area under the curve of receiver operating characteristic) curve. Results. A total of 102 liver cirrhosis patients who experienced first-time esophageal variceal bleeding were included in the study. Recurrent esophageal variceal bleeding was found in 23/102 (22.5%) liver cirrhosis patients. There was a significant difference in spleen stiffness values between the two groups, with higher values in the group of patients with recurrent esophageal variceal bleeding (90.9 kPa (IQR: 86.5 – 96.2) vs. 59.3 kPa (IQR: 45.2 – 74.3), p < 0.001). The AUC value of spleen stiffness for predicting recurrent esophageal variceal bleeding provided good predictability, with an AUC value of 0.898 (95% CI 0.808 – 0.988), p < 0.001. The cut-off value of spleen stiffness at 70 kPa yielded a sensitivity of 87% and specificity of 65% in predicting recurrent esophageal variceal bleeding. Conclusion. Spleen stiffness measurement can be beneficial as an evaluation method to assess the likelihood of recurrent esophageal variceal bleeding in patients with liver cirrhosis at the 6th week after the first bleeding episode.